2020
DOI: 10.1039/d0tc02535f
|View full text |Cite
|
Sign up to set email alerts
|

A simple fabrication of high efficiency planar perovskite solar cells: controlled film growth with methylammonium iodide and green antisolvent sec-butyl alcohol

Abstract: Perovskite films can be prepared using sec-butyl alcohol (2-BA) by a one-step antisolvent assisted method. However, 2-BA dissolves a necessary perovskite precursor, methylammonium iodide, CH3NH3I, (MAI), which is lost during...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Although the peak intensities of I‐4000 and III‐4000 samples were high, an extra PbI 2 peak was observed in approximately 2θ peak at 12.75° for both samples. The lower efficiencies of these samples can be attributed to remaining PbI 2 without conversion to CH 3 NH 3 PbI 3 structure 28,29 . On the other hand, IV‐4000 and V‐4000 are both distinguished with sharp and strong characteristic peaks indicating good crystallinity.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Although the peak intensities of I‐4000 and III‐4000 samples were high, an extra PbI 2 peak was observed in approximately 2θ peak at 12.75° for both samples. The lower efficiencies of these samples can be attributed to remaining PbI 2 without conversion to CH 3 NH 3 PbI 3 structure 28,29 . On the other hand, IV‐4000 and V‐4000 are both distinguished with sharp and strong characteristic peaks indicating good crystallinity.…”
Section: Resultsmentioning
confidence: 95%
“…The lower efficiencies of these samples can be attributed to remaining PbI 2 without conversion to CH 3 NH 3 PbI 3 structure. 28,29 On the other hand, IV-4000 and V-4000 are both distinguished with sharp and strong characteristic peaks indicating good crystallinity.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the high density of deep-level traps that trap either electrons or holes and do not escape by thermal recombination, Shockley–Read–Hall (SRH) statistics are a significant loss mechanism that gives the rate of non-radiative recombination process in perovskites. 73,74 Transparent conductive oxide (TCO) makes up the top layer, which aids in the decay of the photo-excited population through contact. This takes place when the excitation density is low.…”
Section: Defects Of Perovskites In Photovoltaic Applicationsmentioning
confidence: 99%
“…Great progress has been made in this regard in recent years such as applying ester and alcohol. Zhang et al first used sec‐butyl alcohol as the antisolvent and achieved 14.3% PCE in CH 3 NH 3 PbI 3 solar cells and this was further improved by Qiu et al [ 23,24 ] Park et al reported the 17.85% PCE was obtained with 2‐methyl tetrahydrofuran antisolvent treatment in MAPbI 3 ‐based device. [ 25 ] Sec‐pentyl alcohol has been applied to realize a 17% PCE in MAPbBr 3 solar cell.…”
Section: Introductionmentioning
confidence: 99%